2012
DOI: 10.1242/jcs.105015
|View full text |Cite
|
Sign up to set email alerts
|

Polo-like kinase is required for synaptonemal complex disassembly and phosphorylation in mouse spermatocytes

Abstract: During meiosis, accurate coordination of the completion of homologous recombination and synaptonemal complex (SC) disassembly during the prophase to metaphase I (G2/MI) transition is essential to avoid aneuploid gametes and infertility. Previous studies have shown that kinase activity is required to promote meiotic prophase exit. The first step of the G2/MI transition is the disassembly of the central element components of the SC; however, the kinase(s) required to trigger this process remains unknown. Here we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
85
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(90 citation statements)
references
References 56 publications
4
85
0
1
Order By: Relevance
“…In Saccharomyces cerevisiae, APC/C AMA1 targets both cyclin B1 and the yeast PLK1 homolog Polo (Cdc5) to maintain appropriate prophase I timing (Okaz et al, 2012). Consistent with a previous recent study (Jordan et al, 2012) immunohistochemistry revealed chromatin-associated localization of PLK1 in control spermatocytes, which was similar in the few detectable FZR1Δ spermatocytes. Additionally, immunoblotting of D11 testis suggested that PLK1 protein was not prematurely increased in FZR1Δ animals (supplementary material Fig.…”
Section: Cyclin B1 Is Upregulated In Germ Cells Lacking Fzr1supporting
confidence: 92%
“…In Saccharomyces cerevisiae, APC/C AMA1 targets both cyclin B1 and the yeast PLK1 homolog Polo (Cdc5) to maintain appropriate prophase I timing (Okaz et al, 2012). Consistent with a previous recent study (Jordan et al, 2012) immunohistochemistry revealed chromatin-associated localization of PLK1 in control spermatocytes, which was similar in the few detectable FZR1Δ spermatocytes. Additionally, immunoblotting of D11 testis suggested that PLK1 protein was not prematurely increased in FZR1Δ animals (supplementary material Fig.…”
Section: Cyclin B1 Is Upregulated In Germ Cells Lacking Fzr1supporting
confidence: 92%
“…We next examined whether the level of cAMP controls the disassembly and degradation of SYCP1 in oocytes. To assess the disassembly of the SYCP1 protein, we cultured ovaries (16.5 dpc) with MDL-12,330 and performed chromosome spreads and immunofluorescence staining as previously reported (Jordan et al, 2012). In this approach, linear SYCP1 staining indicated that the synaptonemal complex (SC) was integrated with SYCP1, whereas discontinuous or lack of SYCP1 staining indicated disassembly of SYCP1 from the SC (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies demonstrated that separation of the SC is essential for spermatocytes to enter the diplotene stage of meiosis in rodents (Tarsounas et al, 1999;Jordan et al, 2012). Here we show that the level of oocyte cAMP regulates the dissolution of SYCP1 from the SC.…”
Section: Discussionmentioning
confidence: 97%
“…Thus, the inhibition of cell cycle progression is caused by the inhibition of the kinase activity of the PLKs. In fact, Jordan et al have discovered the great importance of PLKs in synaptonemal complex disassembly in mouse spermatocytes by brief in vitro culture of spermatocytes (12). Recently, Cdc5, an ortholog of the PLKs, was found to be a central regulator of meiosis I in yeast (59).…”
Section: Discussionmentioning
confidence: 99%